2009
DOI: 10.1007/s11252-009-0088-9
|View full text |Cite
|
Sign up to set email alerts
|

Exotic plant invasions in forested wetlands: effects of adjacent urban land use type

Abstract: There are a variety of land use types in urbanized areas that may have different effects on the ecological characteristics of patches of natural vegetation. In particular, residential housing and industrial land-use may have different effects on adjacent forest communities. We tested this hypothesis by examining the vegetation of forested wetlands in a densely urban region, northeastern New Jersey. Wetlands embedded in industrial areas were much less invaded by exotic plant species than were wetlands embedded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 54 publications
0
3
1
Order By: Relevance
“…Finally, while the surrounding landscape has been shown to influence the susceptibility of several wetlands to invasion (Findlay and Houlahan 1997;Findlay and Bourdages 2000;Maheu-Giroux and de Blois 2007;Bowman Cutway and Ehrenfeld 2009), we found no effect of the landscape on the level of invasion of peatland intersected by power line ROWs. The low influence of our landscape variables is likely because of the relatively homogenous landscape in the study area.…”
Section: Discussioncontrasting
confidence: 67%
“…Finally, while the surrounding landscape has been shown to influence the susceptibility of several wetlands to invasion (Findlay and Houlahan 1997;Findlay and Bourdages 2000;Maheu-Giroux and de Blois 2007;Bowman Cutway and Ehrenfeld 2009), we found no effect of the landscape on the level of invasion of peatland intersected by power line ROWs. The low influence of our landscape variables is likely because of the relatively homogenous landscape in the study area.…”
Section: Discussioncontrasting
confidence: 67%
“…This shrub produces phenolic compounds (tannins) in its leaves and roots (Dorning and Cipollini 2006;Cipollini et al 2008) that are toxic to native plant taxa (Dorning and Cipollini 2006) and deter generalist herbivores (Cipollini et al 2008). Lonicera maackii can be abundant in urban and suburban forested wetlands (Swab et al 2008;Cutway and Ehrenfeld 2009), and its broad distribution in the eastern and central USA overlaps the geographic ranges of many native amphibians. Because the phytochemicals produced by L. maackii are water-soluble (Cipollini et al 2008), they may be bioavailable to aquatic organisms occurring in invaded wetlands.…”
Section: Introductionmentioning
confidence: 99%
“…In urban areas, fragments of natural vegetation embedded within urban land uses are frequently but not always highly invaded (Moffatt et al 2004;Borgmann and Rodewald 2005;Kowarik 2005;Ehrenfeld 2008). We have found that wetlands embedded within industrial urban land uses are less invaded than those embedded within residential areas (Ehrenfeld 2008;Bowman Cutway and Ehrenfeld 2009); we now address the potential role of seed dispersal in explaining that difference.…”
Section: Introductionmentioning
confidence: 87%
“…Our previous study (Bowman Cutway and Ehrenfeld 2009) demonstrated that the wetland sites were similar in species composition, structure, and levels of disturbance, and experimental tests of the ability of seeds to germinate and produce vigorous seedlings showed that there was no difference in the ability of seedlings to establish (Bowman Cutway 2004), thus eliminating environmental factors as potential confounding variables. In order to test our hypotheses, we measured wetland edge structure, exotic seed source availability on these edges, composition and number of seeds in the wetland seed rain and seed bank.…”
Section: Introductionmentioning
confidence: 98%